Sleep and cognition in the elderly - Julie Carrier (Frontiers Research Topics, 2015)
Understanding the role of sleep and the mechanisms at play in ageing are among the most exciting challenges in neuroscience. Although our understanding of the mechanisms governing sleep stages and their role in cognitive processes including memory functions is gradually increasing. most of the currently available data have been gathered in young adults. Still, substantial physiological changes in sleep are observed with increasing age, that may markedly impacts on daily functioning. This is why this Research Topic focuses on our current understanding of the impact of age-related changes in sleep architecture on various domains of cognition. The three editors Julie Carrier (Montréal, Canada), Philippe Peigneux (Brussels, Belgium) and Géraldine Rauchs (Caen, France) are specialized in various fields of sleep research. Here, they bring together an outstanding group of neuroscientist and clinical investigators engaged in the study of sleep, encompassing state-of-the-art studies of sleep disorders such as sleep apnoea or REM sleep behaviour disorder, studies assessing new treatments to improve sleep quality, together with experts in various domains of cognition such as vigilance, memory and dreams, in a perspective aimed at offering the interested reader a comprehensive view of the impact of age-related changes in sleep architecture on cognition.